Enhancing Arts Teaching and Learning Through Mooc - Mohd Fahmi, Yahaya; Ang, Tse Chwan; Syaryfah Fazidawaty, Wan Busrah; Yow, Chong Lee; Mohd Sharizam, Hamzah; Mohd Affendi, Azizan; Rahah, Hasan; Muhyiddin, Mohammed; Noorhaslina, Senin (Centre for Applied Learning and Multimedia, UNIMAS, 2019)
This project is a collaborative effort by a group of Faculty of Applied and Creative Arts lecturers whom were involved in a MOOC project titled Application of ICT in Applied and Creative Arts. The objectives of this present project are twofold. First, it strives to identify problems rendered by using MOOC in the process of teaching and learning arts courses. Secondly, to enhance the use of MOOC by proposing solutions to the problems. Throughout the implementation of our MOOC project, it was found that while we were able to assess students’ understanding of the theoretical part of the project through quizzes, essays and polls, it was rather difficult to observe their overall process of completion such as drawing techniques, lighting set-ups for video production, reading notes and playing musical instruments, character design and other crucial elements that needs to be assessed.